Dealing with the unknown. A proposal for a method for redistributing skeletons of unknown sex and age in an assemblage - Tony Waldron (Papers from the Institute of Archaeology, 2012)
One of the first jobs for any bone specialist examining an assemblage is to assign an age at death and a sex to the individual skeletons. Having done so, he or she will then construct a table in which the number of skeletons in each of the age and sex categories is shown. An example is shown in table 1, based on the published account of the assemblage from Barton-on-Humber in Lincolnshire (Waldron, 2007a). It can be seen that there are a substantial number of skeletons for which neither the sex nor the age (or both) can be determined. None of the sub-adults has been given a sex, since there are no wholly reliable ways to sex the juvenile skeleton as the skeleton is not sufficiently dimorphic before the onset of puberty; there are several skeletons which have been given an age but no sex; and a considerable number of adults (446 or about 16% of the total) for which neither age nor sex could be assigned. The number of 'known unknowns' in this assemblage is high but by no means unusual, and, in general, is directly related to the state of preservation; the poorer the preservation, the greater the number of skeletons that cannot be given an age or a sex.
Keywords: age and sex distribution; skeletons; human remains